CLINICAL-ANATOMICAL BASIS FOR CUTTING TISSUES OF THE HEAD AREA (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article delves into the critical importance of understanding the clinical-anatomical basis for cutting tissues in the head area during medical procedures. Through an extensive literature review and analysis, this work aims to elucidate the relevance and significance of this topic, shedding light on the intricate anatomical structures and their clinical implications. The methods, results, and discussion sections provide a comprehensive overview of the current state of knowledge in this field, offering insights that can enhance surgical practices and medical education. The article concludes with key takeaways and suggestions for further research.